(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
The Pro-Huerta program delivers the autumn-winter and spring-summer seasonal seed kits free of charge to all INTA agencies. Each seed kit removed from the agency by the beneficiary, is registered in a form with the information of the address where the vegetable garden will be and a contact number. Using the data and a geographic information system (GIS), it was possible to georeference the potential vegetable gardens in the city of Río Cuarto, becoming a tool for intervention and territorial accompaniment of the extension agency in order to plan the survey and monitoring of activities productive of them.